Where crises converge: the affective register of displacement in Mexico City's post-earthquake gentrification. (April 2021) - Linz, Jess
Affect theory suggests that imagining different futures for cities begins by feeling the present differently. This article considers the political potential of the affective register in the context of gentrifying Mexico City, where the 2017 earthquake, as a crisis-event, burst onto the ongoing crisis-ordinary of gentrification-based displacement. I argue that this convergence of crises opened an affective impasse, or a time and space lived in excess of predictability. This affective impasse both interrupted business-as-usual gentrification and channeled historical affects across 32 years from the 1985 earthquake, and in turn generated new political energies. Informed by affect theory and trauma studies, I use qualitative data to invite the reader into the impasse and observe its affective dynamics. The empirical sections describe the entry points to the impasse, the affective activities that subjects engage in there, and the role of historical trauma in reshaping the atmospheres that emerge from this space. The resulting research investigates how affective ways of navigating an impasse offer the potential to reshape ongoing struggles against displacement. This builds on recent work in urban geography that uses psychoanalysis and affect theory to understand gentrification's complexities, contradictions, and ambivalences.